Ideological Seduction and Intellectuals in Putin's Russia - Shlapentokh, Dmitry. author. aut Link
IX, 283 p. 1 illus.
Keywords: This book examines the interplay between key rulers and intellectuals in creating and sustaining popular discourses that often help keep rulers in power. By focusing in particular on the relationship between Putin and Dugin during the early Putin regime, the author zooms in on the questionable honesty in Putin's interest in Dugin's philosophy, and the instrumentality of that philosophy for strategic regime building. Arguing that ideology is largely supported by political philosophies that gain popular traction, the book questions the extent to which rulers are likely to stay faithful to their stated ideologies. Providing on-the-ground insight into Putin's rule, this book appeals to researchers and policymakers studying Post-Soviet Politics. Dmitry Shlapentokh is Associate Professor of History and Politics at Indiana University, South Bend.